The Impacts of Working Conditions and Employee Competences of Fresh Graduates on Job Expertise, Salary and Job Satisfaction - Hsiao, Jui-Min; Lin, Da-Sen (Journal of Reviews on Global Economics, 2018)
This study explores the factors that have critical impacts on job expertise and further analyses on how the jobs affect salary and job satisfaction. Job seekers consider the working conditions when seeking jobs. However, he/she will acquire an ideal job or not, it depends on his/her employee competences. The former is his/her job demands and expectations and the latter is the ability he/she has. These two factors determine his/her job expertise which further influences the salary and job satisfaction. The data are collected from those new graduates who entering the workforce from Taiwan’s universities in 2009 and structural equation modeling is applied for data analysis. Three findings are presented. First of all, the correlation coefficient is 0.40 which indicates strong relationship when it comes to the relation of employee competences and working conditions. Secondly, employee competences have significantly positive impacts on job expertise, salary and job satisfaction. However, working conditions have significantly negative impacts on salary. Finally, job expertise has significantly positive impacts on salary and job satisfaction but salary has no significant impacts on job satisfaction.